A guide to feeding and assessment of calf milk replacer. Issue 6 (November 2013) - Cooper, Richard; Watson, Ian
<x xml:space="preserve">Abstract</x> The health, productivity and welfare of neonatal and young calves is heavily influenced by nutrition. In the UK, using a commercial calf milk replacer in place of dam's milk is extremely common practice, usually driven by economic and infectious disease control advantages. This article aims to examine some of the considerations for selection of a calf milk replacer and practical aspects of feeding, in order to maximise calf growth rates, health and future productivity.